SOLUTION OF AN INVERSE PARABOLIC PROBLEM WITH UNKNOWN SOURCE-FUNCTION AND NONCONSTANT DIFFUSIVITY VIA THE INTEGRAL EQUATION METHODS (Journal of Sciences, Islamic Republic of Iran)
In this paper, a nonlinear inverse problem of parabolic type, is considered. By reducing this inverse problem to a system of Volterra integral equations the existence, uniqueness, and stability of the solution will be shown.